Infrastructure's Imprint: Metro Proximity and Property Development Dynamics in S\~ao Paulo, Brazil - Daniel Grimaldi; Oscar A. Mitnik; Beatrice Zimmermann (Institute of Labor Economics (IZA), 2024)
How does the proximity to a metro station affect urban development in Latin America? While the literature assessing the causal impacts of transportation infrastructure has grown in recent years, only a few papers have focused on the effects of metro systems in Latin America and the Caribbean (LAC) region, and identifying the precise impacts of such investments is far from straightforward. We apply a Synthetic Difference-in-Differences (SDiD) approach to estimate the effects of the expansion of Line 5 of the S\~ao Paulo metro system in Brazil on land use and property features. Our results show positive impacts on constructed area, with a treatment effect that is half the magnitude of the average constructed area in untreated units in the pre-treatment period. Additionally, our findings indicate an increase in the number of properties around the stations, with a shift in property composition towards more commercial units. We also find a strong anticipation effect associated with the new metro infrastructure and dynamic impacts after the opening of the first metro station, with effects that increase over time.
Keywords: R14; R40; R42; 330; land use; infrastructure investments; impact evaluation